A Review of Banking Sector in India: Adapting to Technological Innovations and Global Challenges (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today, the banking industry in our country is stronger and capable of withstanding the pressures of competition. It withstood Global Financial Crisis (2008). In the era of Globalization Banking Sector in India is rapidly changing since 1990s due to technological innovation, financial liberalization with entry of new private and foreign banks, and regulatory changes in the corporate sector. Indian banking industry is gradually moving towards adopting the best practices in accounting, internationally accepted prudential norms, with higher disclosures and transparency, corporate governance and risk management, interest rates have been deregulated, while the rigour of directed lending is being progressively reduced. In our country, currently we are having a fairly well developed banking system with different classes of banks – public sector banks, foreign banks, private sector banks – both old and new generation, regional rural banks and co-operative banks with the Reserve Bank of India as the leader of the system. In the banking field, there has been an unprecedented growth and diversification of banking industry and our banks are now utilizing the latest technologies like internet and mobile devices to carry out transactions and communicate with the masses.